Formulation Development And In Vitro- Assesment Of Herbal Anti-Bacterial Cream - Tokbi, Ratsongja; Vyas, Girish Kumar; Sharma, Hariom; Sharma, Anil; Sharma, Manmohan (Asian Journal of Pharmaceutical Research and Development, 2023)
Objectives of the study: To evaluate various formulation factors and the topical cream formulation of Cassia Siamea flower extract for antibacterial activity. Phytochemical screening and characterization of the topical formulation (cream) made from the alcoholic extract are done after the extraction of Cassia Siamea. Materials and Methods:A suitable procedure was used to gather and extract the plants. The yield of the extract was estimated after drying. The broth dilution method was used to determine the MIC. This made it easier to determine the formulation's yield quantity. This yield was used to create cream, after which evaluations were conducted to test the product's quality. Results and Discussions: Began with the extraction and was followed by confirmation of the phytochemical evaluation. According to the confirmatory study, the ethanolic extract was devoid of saponins and glycosides. Tannins, phenolics, flavonoids, and alkaloids were also discovered, but not these carbohydrates. In MIC testing, the Cassia Siamea flower extract shown good activity and effectively inhibited the growth of Propionibacterium acnes and Pseudomonas aeruginosa. The designed composition produced a very smooth cream. In accordance with I. P., evaluations were also discovered to be within the range of conventional formulas. Evaluations revealed that the overall formulation had good activity against microorganisms. Conclusion: This study reveals that a range of phytochemicals are present in Cassia siamea flowers as an active component, producing positive findings against antibacterial activity and showing great promise as an antibacterial agent. This study also comes to the conclusion that the extraction of Cassia Siamea flowers is essential for the development of better, safer, and more affordable drugs to treat different bacterial illnesses.